VARIABEL-VARIABEL PENENTU EKSPOR RIIL INDONESIA PERIODE TAHUN 2000 – 2015 (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2017)
This study aimed to analyze the real determinants of Indonesian exports. in the year 2000-2015. This study used three models, where the research dependent variables were real exports of Indonesian oil and gas, Indonesia non oil and gas real exports, and Indonesia total real exports. While the independent variables were the real exchange rate of rupiah against the US dollar and the real Gross Domestic Product of the world for the three models. The analysis technique used was multiple linear regressions. The research concluded that the real exchange rate of rupiah against US dollar Indonesia was sufficient evidence negative and significant impact to real exports of Indonesian oil and gas, Indonesia non oil and gas real exports, and Indonesia total real exports. Furthermore, the real Gross Domestic Product of the world was sufficient evidence to positively and significantly affect the same three dependent variables. The effect of rupiah real exchange rate on US dollar and real world gross domestic product to real exports of Indonesian oil and gas is bigger than to Indonesia non oil and gas real exports, and Indonesia total real exports. Meanwhile, the real Gross Domestic Product of the world is greater than the real exchange rate of rupiah against the US dollar against the three dependent variables. Indonesia still has to manage the real exchange rate of rupiah against the US dollar so that it can boost Indonesia's exports. Likewise, the positive trend of the world's growing economic development, which will then increase the real gross domestic product of the world, will have an increasing impact on Indonesia's exports.